A molecular modeling approach to understand the structure and conformation relationship of (GlcpA)Xylan. (10th December 2015) - Guo, Qingbin; Kang, Ji; Wu, Yan; Cui, Steve W.; Hu, Xinzhong; Yada, Rickey Y.
Highlights: Computer modeling was applied for the conformational study of (Glc p A)Xylan from Artemisia seeds. Adiabatic potential energy surface of disaccharides were studied. RIS-Metropolis Monte Carlo (RMMC) method was applied. The ratio Glc p A showed obvious effects on the conformation of Xylan backbone. The distribution of Glc p A influenced the Xylan chain flexibility in a specific manner. Abstract: The structure and conformation relationships of a heteropolysaccharide (Glc p A)Xylan in terms of various molecular weights, Xyl p /Glc p A ratio and the distribution of Glc p A along xylan chain were investigated using computer modeling. The adiabatic contour maps of xylobiose, Xyl p Xyl p (Glc p A) and (Glc p A)Xyl p Xyl p (Glc p A) indicated that the insertion of the side group (Glc p A) influenced the accessible conformational space of xylobiose molecule. RIS-Metropolis Monte Carlo method indicated that insertion of Glc p A side chain induced a lowering effect of the calculated chain extension at low Glc p A:Xyl p ratio (Glc p A:Xyl p = 1:3). The chain, however, became extended when the ratio of Glc p A:Xyl p above 2/3. It was also shown that the spatial extension of the polymer chains was dependent on the distribution of side chain: the random distribution demonstrated the most flexible structure compared to block and alternative distribution. The present studies provide a unique insight into the dependence of both side chain ratio and distribution on the stiffness and flexibility of various (Glc p A)Xylan molecules.